Modeling Blast Loading on Buried Reinforced Concrete Structures with Zapotec - Greg C. Bessette (Shock and Vibration)
A coupled Euler-Lagrange solution approach is used to model the response of a buried reinforced concrete structure subjected to a close-in detonation of a high explosive charge. The coupling algorithm is discussed along with a set of benchmark calculations involving detonations in clay and sand.